Firm's price expectations: An empirical analysis using BCRAs' Survey of Business Economic Perspectives - Pedro Elosegui; Máximo Sangiácomo (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2022)
The Central Bank of Argentina (BCRA) implements a monthly Survey of Business Economic Perspectives to capture the business climate and economic perspectives. The survey, includes both qualitative and quantitative questions on past and expected change in different economic variables of the main companies in Argentina. This unique proprietary data is used to approximate the price setting behaviour of the firms in the domestic markets. We postulate an econometric model where the firms' dynamic on their expected domestic prices are based on (i) firm's past and expected information (prices, input costs and inventories) and (ii) macroeconomic variables (economic activity, foreign exchange rate, interest rate and inflation rate). The results indicate the importance of input costs (domestic and imported) and the macroeconomic variables (especially the exchange rate and the inflation rate) in the expected price dynamics of the analyzed companies and are in line with the literature analyzing price setting behaviour under macroeconomic uncertainty. Foreign exchange rate pass-through, markups on input prices and forward-looking behaviour in price setting generate important challenges for the anti inflationary monetary policy.
Keywords: E30; E50; D40; 330; Survey data; Price setting; Firms Expectations